Prediction of Wear Rate by a New Direct Method Using the Friction Coefficient Curve - Ester Villanueva; Joseba Albizuri; Patricia Caballero; Teresa Guraya; Iban Vicario (Journal of Manufacturing and Materials Processing)
This work aims to introduce a new method to predict the wear rate accurately and quickly. Using techniques such as laser scanning confocal microscopy can take a long time to estimate the wear of the experimental alloys in situ. Developing a new method based on calculating the area under the early stages of the friction curve can be a useful and quick tool for estimating wear rate values and comparing wear between different alloys and conditions. The results validated the application of this new method with a regression coefficient of 0.98. This work also demonstrates that wear in the early stages accounts for the highest wear, indicating that the friction coefficient in the steady-state is not always a reliable indicator of the total wear rate. Hardness can be a more influencing parameter on wear rate than steady-state friction coefficient. Using the new method can help reduce time and predict wear more accurately of different alloys.